Perkembangan Hukum Positif Indonesia Dalam Mempengaruhi Kebebasan Berpendapat Masyarakat - Cindy Permata; Davina Asya Shafira; Fadiah Tarisa Sabrina; Meira Lalia Ayuningtyas; Rebecca Purba; Sandra Amelia; Mulyadi M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Indonesia, as a democratic country, guarantees its citizens the privilege of free expression. Allowing freedom of expression does not imply complete freedom, because Indonesia, as a democratic country, has rules in place to ensure peace and the well-being of its citizens. Freedom of expression in social life is expected to have an impact on the country's development and progress by attaching to various existing regulations and taking responsibility for their actions. The research method used is normative juridical, which focuses on studying the formulation of the problem by collecting legal data in the form of laws and research journals that regulate Indonesia's right to free expression. The conclusions show that positive law in Indonesia has evolved in accordance with social transformation, such as the passage of the 1945 Constitution of the Republic of Indonesia Article 28E paragraph (2) and Article 1 paragraph (1) of Law No. 9 of 1998, Law No. 40 of 1999 concerning the Press, and UU no. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, which regulate legal protection for the public.